Dietary intake as a cardiovascular risk factor: a cross-sectional study of bank employees in Accra. Issue 2 (2nd April 2020) - Frimpong, Ivy Priscilla; Asante, Matilda; Maduforo, Aloysius Nwabugo
Abstract : Objectives: To determine the dietary and nutrient intakes of bank employees in Accra in relation to recommended dietary intake for the control of cardiovascular diseases (CVD). Design: The study was a cross-sectional study. Methodology: A structured validated questionnaire was used to obtain demographics. A 3-day 24-hour dietary recall and usual food intake questionnaire were used to obtain information on food intakes and dietary pattern of the respondents. Food models, household measures and photos of common dishes as well as household cups and measures were used in order to obtain accurate information regarding the types and quantities of foods and beverages consumed. Subjects: Convenient sampling was used to select bank branches while simple random sampling by ballot without replacement was used to select 119 bank employees who consented to participate in the study. Outcome measures: Data were analysed using Statistical Package for the Social Sciences software. Esha FPro software was used to analyse food nutrients. The nutrient intakes were compared with a standard dietary guideline for adults. Results: Findings showed significant ( p  < 0.05) differences in mean energy intake between males and females. Also, the bank employees were consuming more fat (32%) compared with the recommended intake. The average intake of dietary sodium and cholesterol was within the recommended intake levels. All the participants in the study had a mean intake of dietary potassium, fibre, fruits and vegetables below the recommended levels. The major cooking oils used in meal preparation were vegetable and palm oil (46%), followed by vegetable oil (31.9%) and palm oil (21.8%). Conclusions: The study evaluated the dietary intake of bank employees, which is an important risk factor for chronic diseases. There is a need to develop plans to provide nutrition education and counselling for adequate nutrient intake and prevention of chronic diseases among bank employees. Layman's summary: Obtaining an adequate diet and avoiding overconsumption of food helps to maintain health. Intake of foods containing high energy and fats without corresponding energy expenditure through physical activity could result in obesity, heart diseases, diabetes and other health challenges. Inadequate intake of micronutrients as well could result in deficiency diseases, and depresses the immune system and health of individuals. Bank employees and all other individuals need to pay attention to what they eat to live a healthy and longer life. Regular physical activity, following the dietary approaches to avoid hypertension and regular medical check-up are essential for cardiovascular health. Strong lay message: Inadequate or overconsumption of nutrients can cause chronic heart diseases.